Diagnóstico de leptospirose bovina em duas propriedades rurais utilizando MAT, ELISA e PCR - Rezende, Laís Miguel (2016)
Leptospirosis is a disease of great economic impact on livestock as well as being an important zoonosis that affects several animal species. Several serotypes can infect cattle, inducing or no clinical manifestations thus clinical diagnosis is inconclusive, requiring the help of laboratory tests to confirm the diagnosis. may or may not induce clinical manifestations clinical diagnosis is not conclusive, requiring support of laboratory tests to confirm the diagnosis. The Microagglutination test (MAT) is considered as standard by the World Organization for Animal Health (OIE) but has some limitations and their interpretation can be suggestive. Some tests in order to detect anti-Leptospira immunoglobulins are being developed in order to replace it or supplement it, as ELISA and PCR. They can act as allies in animal tracking, because they are more sensitive and specific tests, increasing the quality of the diagnostic procedure. The aim of this research is to evaluate the occurrence of infection in two properties, with and without history of leptospirosis with support of MAT, ELISA and PCR. For this were analyzed 48 cows, of these 20 (41.66%) were positive in MAT, with antibody titers equal or greater to 100, 12 urine samples were selected for PCR analysis are all considered negative to the test. To complement the results, three ELISAs, each employing different antigens to detect antibodies in cattle sera, these being: L.interrogans serovar Hardjo, L.interrogans serovar Hebdomadis and a pool with six serotypes have been developed. They presented as sensitivity, 90%, 70%, and 20% respectively, and a specificity of 67, 10%, 80, 26%, 89, 47%. Except the ELISA / pool, all have reached a good agreement with the standard test and good reproducibility. In conclusion, it is always important to relate two or more diagnostic tests, associated with the clinical diagnostic, to increase the effectiveness of the results.